AB0397 Treatment Refractory Rheumatoid Arthritis: Is Repository Corticotropin Injection (RCI) An Effective Option in Patients Resistant To Biologic Therapies? (A Pilot Study). (15th July 2016) - Fischer, P.; Rapoport, R.
Abstract : Background: Despite the availability of therapeutic options for RA, including DMARDs and biologic agents, there are many patients who are resistant to current therapy and remain inadequately controlled. We hypothesized that 12-week repository corticotropin injection (RCI) treatment may provide relief of RA and acute exacerbations in patients refractory to treatment with DMARDs and at least three biologics (including 1 tumor necrosis factor inhibitor). Objectives: The objective of this study was to assess the efficacy and safety of RCI in this patient population. Methods: This was a 12-week prospective, multicenter, open-label study with 9 patients. Patients were maintained on stable doses of a biologic, other DMARD therapies and prednisone of at least 7.5 mg daily; RCI was adjunctive therapy. RCI 40 U was given subcutaneously daily for 7 days. If an adequate response (>1.2 point reduction in the Disease Activity Score 28 using C-Reactive Protein [DAS28-CRP]) was achieved, the dose was decreased to 40 U twice weekly through week 12. If the response was inadequate, patients received 80 U once daily for 7 days, followed by 80 U twice weekly through week 12. The primary endpoint was >1.2 point reduction in DAS28-CRP at week 12. Secondary endpoints included improvements in American College of Rheumatology 20%, 50%, and 70% (ACR20, 50 and 70), decrease in Health Assessment Questionnaire Disease Index (HAQ-DI) score, and improvement in Functional Assessment of Chronic Illness Therapy (FACIT) and health-related quality of life (HRQOL) questionnaires. Results: We report results for 9 patients (44–60 years). A total of 66% (6/9) of patients met the primary endpoint. The mean DAS improvement at 12 weeks on 40 U of therapy was numerically greater than that in patients increasing their dose to 80 U. Improvements were also noted in secondary endpoints, particularly over the first 4–8 weeks of treatment. Five of 9 patients maintained improvement in HAQ-DI and in the FACIT fatigue scale at week 12 (Table). There did not appear to be a clear pattern or association between cortisol levels and RCI response. No serious adverse events (AEs) occurred. Mild AEs included Cushingoid features (n=2), mild hyperglycemia (n=1), herpes zoster (n=1), and pedal edema (n=1). Conclusions: RCI produced a rapid and clinically meaningful reduction in markers of disease activity and improved quality of life. RCI demonstrated a favorable safety profile; there were no serious adverse events and cortisol levels did not increase for most patients. For patients who are refractory to common RA therapies, the response rate to RCI was substantial and shows great promise in this difficult to treat population. Disclosure of Interest: P. Fischer Grant/research support from: Mallinckrodt, Genetech, Paid instructor for: Mallinckrodt, R. Rapoport Paid instructor for: Amgen, Abbvie, Union Chimique Belge, Exagen